2018
DOI: 10.3906/kim-1711-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation and synthesis of new pyrimidine-2(1H)-ol/-thiol derivatives derived from chalcones using the solid phase microwave method

Abstract: Twenty-five new hydroxy-and methoxy-substituted 4,6-diarylpyrimidin-2(1H)-ol (20-34) and 4,6-diarylpyrimidine-2(1H)-thiol derivatives (35-44) were synthesized from the reaction of the corresponding 1,3-diaryl-2-propene-1one compounds (1-19) with urea or thiourea using the solid-phase microwave method. All the new synthetic compounds (20-44) were evaluated with regard to their α-glucosidase activity. However, only compounds 22-25, 27, 31, 34, 35, 37, and 40 exhibited a greater inhibitory effect than standard ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Fandakli et al, (2016; 2018) used a solid-phase microwave method to synthesis 25 new hydroxy-and methoxy-substituent 4,6-diarylpyrimidine-2(1H)-ol and 4,6 diarylpyrimidine-2(1H)-thiol pyrimidine compound derivatives and evaluate their gram-negative and grampositive antibacterial activities, α-glucosidase activity and in vitro pancreatic lipase activity. Besides the antilipase activity and the inhibitory effects on αglucosidase, results showed that some of these original pyrimidine drivetives possess significant activity against Escherichia faecalis, Staphylococcus aureus, Bacillus cereus and Mycobacterium smegmatis with minimum inhibitory concentrations between 62.5 and 500 µg/mL [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fandakli et al, (2016; 2018) used a solid-phase microwave method to synthesis 25 new hydroxy-and methoxy-substituent 4,6-diarylpyrimidine-2(1H)-ol and 4,6 diarylpyrimidine-2(1H)-thiol pyrimidine compound derivatives and evaluate their gram-negative and grampositive antibacterial activities, α-glucosidase activity and in vitro pancreatic lipase activity. Besides the antilipase activity and the inhibitory effects on αglucosidase, results showed that some of these original pyrimidine drivetives possess significant activity against Escherichia faecalis, Staphylococcus aureus, Bacillus cereus and Mycobacterium smegmatis with minimum inhibitory concentrations between 62.5 and 500 µg/mL [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The MDA and GSH levels and CAT activity were evaluated as endpoints of oxidative stress, one of the most important mechanisms of action of anticancer agents in cancerous cells. The tested pyrimidine derivatives ( Figure 1) were synthesized according to method of Fandakli et al [13,14]. Brifely, 15 mL of chloroform was used to dissolve urea (or thiourea), Methoxy-and hydroxysubstituted 1,3-diaryl-2-propene-1-one (4 mmol of each).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations